DEFENSE MECHANISM OF THE MAIN CHARACTER IN KHALED HOSSEINI’S NOVEL A THOUSAND SPLENDID SUNS - E. Doe, Shesi Meilan; Podungge, Rusni; Usu, Novi Rusnarty (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2023)
This research aims to see how Mariam as the main character in the novel A Thousand Splendid Suns can defend herself against the conflicts she faced. Khaled created the character of Mariam to support the storylines, which actually focuses on showing the war conditions in Afghanistan around the 1970s. The research uses psychoanalysis approach and Freud's defense mechanism theory to analyze Mariam's personality and see how she can survive all the conflicts. This is also use qualitative method to analyze the data. The data is taken from the novel A Thousand Splendid Suns by Khaled Hosseini itself by looking at the text, narration, conversation, plot and setting in the story. Thus, the result of this research indicate that there are several conflicts faced by Mariam, namely social conflict where she is not accepted in the society because of her status as an illegitimate child, conflict with her mother who regrets giving birth to her, conflict with her husband who commits domestic violence and also remarry and conflict with herself where she often blamed herself for all the bad things in her life. In dealing with some of the conflicts above, the researcher found that Mariam overcomes her anxiety and fear problems using defense mechanisms including; repression, reaction formation, denial, displacement, projection, rationalization, undoing, and fantasy. Those defense mechanisms keep her alive and accept the fate that God had been gave to her.